Climate Change Expectations and Endogenous Economic Growth in the DICE Model - Anna Sophia Ciesielski (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper studies the investment based growth rate effects of climate change. The analysis is based on the Integrated Assessment Model DICE by Nordhaus (2008). I depart from the original model, in that endogenous investments into a knowledge stock drive economic growth. Due to a negative capital accumulation as well as savings effect on the knowledge stock, climate change has a negative impact on gross income that lasts into the long run. In order to be able to quantify the growth rate effects, I calibrate the endogenous growth model version of DICE towards its exogenous growth counterpart. I find that in the exogenous growth model version of DICE, compared to its endogenous growth equivalent, in the social optimum, gross income is over-estimated by 2.3 % in 2100 and by 6.8 % in 2150.
Keywords: O44; Q54; 330; endogenous economic growth and climate change